Effects of introducing functional groups on the performance of phenoxazine-based dye-sensitized solar cells. (March 2019) - Bae, Jong Hyuk; Lim, Seung Ju; Choi, Jun; Yuk, Sim Bum; Namgoong, Jin Woong; Ko, Jae Hoon; Lee, Woosung; Kim, Jae Pil
Abstract: Phenoxazine dyes with a hexyloxy chain and furan moiety were synthesized and used in dye-sensitized solar cells. The dyes were designed to investigate the effects of these substituents on the photophysical and electrochemical properties of the dyes and on cell photovoltaic performance. The introduced hexyloxy moiety, as an additional donor, improved the short-circuit current and open-circuit voltage of the cell by increasing light absorption and steric hindrance, respectively. The furan moiety introduced in the phenoxazine dye as a bridge unit led to a bathochromic shift of the absorption band and a large amount of dye adsorption, increasing the short-circuit current of the cell. Among the synthesized dyes, those with the furan moiety showed the best conversion efficiency of 6.34%. Highlights: Effects on the cell performance by hexyloxy and furan group introduced on the phenoxazine dye. Increase of open-circuit voltage current by suppressing charge recombination. Increase of short-circuit current by bathochromic shift and a large amount of dye adsorption. The best efficiency was shown by a cell based on the dye with a furan unit.